Continuous Adductor Canal Blocks: Does Varying Local Anesthetic Delivery Method (Automatic Repeated Bolus Doses Versus Continuous Basal Infusion) Influence Cutaneous Analgesia and Quadriceps Femoris Strength? A Randomized, Double-Masked, Controlled, Split-Body Volunteer Study. (May 2016) - Monahan, Amanda M.; Sztain, Jacklynn F.; Khatibi, Bahareh; Furnish, Timothy J.; Jæger, Pia; Sessler, Daniel I.; Mascha, Edward J.; You, Jing; Wen, Cindy H.; Nakanote, Ken A.; Ilfeld, Brian M.
Abstract : BACKGROUND: It remains unknown whether continuous or scheduled intermittent bolus local anesthetic administration is preferable for adductor canal perineural catheters. Therefore, we tested the hypothesis that scheduled bolus administration is superior or noninferior to a continuous infusion on cutaneous knee sensation in volunteers. METHODS: Bilateral adductor canal catheters were inserted in 24 volunteers followed by ropivacaine 0.2% administration for 8 hours. One limb of each subject was assigned randomly to a continuous infusion (8 mL/h) or automated hourly boluses (8 mL/bolus), with the alternate treatment in the contralateral limb. The primary end point was the tolerance to electrical current applied through cutaneous electrodes in the distribution of the anterior branch of the medial femoral cutaneous nerve after 8 hours (noninferiority delta: −10 mA). Secondary end points included tolerance of electrical current and quadriceps femoris maximum voluntary isometric contraction strength at baseline, hourly for 14 hours, and again after 22 hours. RESULTS: The 2 administration techniques provided equivalent cutaneous analgesia at 8 hours because noninferiority was found in both directions, with estimated difference on tolerance to cutaneous current of −0.6 mA (95% confidence interval, −5.4 to 4.3). Equivalence also was found on all but 2 secondary time points. CONCLUSIONS: No evidence was found to support the hypothesis that changing the local anesthetic administration technique (continuous basal versus hourly bolus) when using an adductor canal perineural catheter at 8 mL/h decreases cutaneous sensation in the distribution of the anterior branch of the medial femoral cutaneous nerve. Abstract : Published ahead of print February 9, 2016